2017
DOI: 10.1098/rsob.170001
|View full text |Cite
|
Sign up to set email alerts
|

Novel layers of RNA polymerase III control affecting tRNA gene transcription in eukaryotes

Abstract: RNA polymerase III (Pol III) transcribes a limited set of short genes in eukaryotes producing abundant small RNAs, mostly tRNA. The originally defined yeast Pol III transcriptome appears to be expanding owing to the application of new methods. Also, several factors required for assembly and nuclear import of Pol III complex have been identified recently. Models of Pol III based on cryo-electron microscopy reconstructions of distinct Pol III conformations reveal unique features distinguishing Pol III from other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 111 publications
(241 reference statements)
0
33
0
Order By: Relevance
“…We thus postulated that Rbs1 protein functions as an assembly/import factor for the Pol III complex [10]. Numerous previous studies concerning the biogenesis of multi-subunit RNA polymerases suggest that the Pol III complex is assembled in the cytoplasm with the help of assembly factors and then transported to the nucleus where it transcribes tRNA genes (reviewed in [13,14]).…”
Section: Introductionmentioning
confidence: 98%
“…We thus postulated that Rbs1 protein functions as an assembly/import factor for the Pol III complex [10]. Numerous previous studies concerning the biogenesis of multi-subunit RNA polymerases suggest that the Pol III complex is assembled in the cytoplasm with the help of assembly factors and then transported to the nucleus where it transcribes tRNA genes (reviewed in [13,14]).…”
Section: Introductionmentioning
confidence: 98%
“…Pol III transcription is hence tightly regulated in response to stress and growth signals, and several signaling pathways converge to modulate the function of the Pol III machinery including its central negative regulator, Maf 2,6 . Maf1 is conserved across eukaryotes, and has been studied in yeast, flies, worms, plants, parasites and mammalian systems (reviewed in 7,8 ). Recently, it was demonstrated that overexpression of Maf1 in the gut of flies increases the lifespan of these animals 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of Pol III in the response to stress (12), we assessed the genome occupancy of TFIIIC in T47D breast cancer cells growing in normal condition (+S) and after 16 Ferrari et al 2019 4 h of SS (-S) ( fig. S1A), which did not alter significantly the cell cycle profile (fig.…”
Section: Introductionmentioning
confidence: 99%